GENDER AND AGRICULTURAL DEVELOPMENT IN DELTA STATE, NIGERIA: AN ANALYSIS OF RURAL WOMEN`S CONTRIBUTIONS AND CHALLENGES - Anugwo, S.C.; Egwue, O.L. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined Gender and Agricultural Development In Delta State, Nigeria: An Analysis of Rural Women`s Contributions and Challenges. Multi-stage sampling procedure was used in selecting 128 respondents. Data were collected using structured questionnaire and analyzed using descriptive statistics such as mean, percentages and likert scale. The results revealed that the mean age of the respondents was 28years with mean household size of 7persons. Majority of the respondents were married with many of them having primary school level of education as their highest level of education and with mean years of farming experience being 6.2years. Agricultural activities performed by the respondents that helped in agricultural development included sourcing for seeds from ADP, use of family labor on the farm, practicing soil conservation tillage. The respondents perception about agricultural development showed that it was a profitable enterprise for women farmers to venture in, they also believed that women farmers participating in agriculture positively impacted their productivity and output and women farmers have the potential to significantly contribute to the sustainable development of the agricultural sector in the study area. Women farmers faced constraints like lack of safety in rural areas, lack of capital, lack of training, and no gender based programs. It is recommended to increase the awareness of the important role that women farmers play in agricultural development and to lessen constraints by enacting laws providing safety, credit, trainings and gender based programs, cheap labor and protecting land rights so women can function better in the study area.